2019
DOI: 10.1248/bpb.b19-00349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Placenta Extract (Laennec) on Ligament Healing in a Rodent Model

Abstract: Rich in bioactive substances such as amino acids and peptides, Laennec (human placenta hydrolysate) has been widely used to control various types of musculoskeletal pain. However, the effects of Laennec on tendon and ligament injuries are not clearly understood. In the present study, Laennec was tested to identify its in vivo effects on ligament injury in an animal model and its in vitro effects on tendon-derived fibrocytes. A total of 99 Sprague Dawley rats were divided into the negative control (normal) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…Animal studies have shown these placental disc extracts reduce concentrations of free radicals and inflammatory cytokines, as well as increase the proliferation of progenitor cells in vitro [ 2 ]. Use of a human placental disc hydrolysate in ligament healing of a rodent model showed marked anti-inflammatory effects, though did not impact structural characteristics of the ligament [ 250 ]. Similarly, a pharmaceutical hydrolyzed extract had antioxidative and anti-apoptotic effects, having a positive impact on skin flap survival in a rat model [ 251 ].…”
Section: Placental Discmentioning
confidence: 99%
“…Animal studies have shown these placental disc extracts reduce concentrations of free radicals and inflammatory cytokines, as well as increase the proliferation of progenitor cells in vitro [ 2 ]. Use of a human placental disc hydrolysate in ligament healing of a rodent model showed marked anti-inflammatory effects, though did not impact structural characteristics of the ligament [ 250 ]. Similarly, a pharmaceutical hydrolyzed extract had antioxidative and anti-apoptotic effects, having a positive impact on skin flap survival in a rat model [ 251 ].…”
Section: Placental Discmentioning
confidence: 99%
“…ГПЧ поддерживал число активированных макрофагов, аналогичное интактной группе. В результате применения ГПЧ отмечены более низкие уровни дегенеративных изменений через 4 нед после лечения, повышенная экспрессия коллагена I типа и теномодулина в хондроцитах (p<0,05) [44]. Интересно также отметить, что ГПЧ поддерживал дифференциацию и ангиогенез в ткани пульпы зубов, способствуя образованию дентина, одонтобластических слоев и дентинальных канальцев [45].…”
Section: лечение заболеваний суставов и костной тканиunclassified
“…PE contains a variety of compounds including nucleic acids, amino acids, peptides, and minerals, which may have positive effects in alleviating various diseases. Recently, several nonclinical studies showed the e cacy of PE as an anti-in ammatory, regenerative, and immunoregulatory agent [13][14][15][16]. A previous study demonstrated the effect of PE in suppressing in ammation using a RAW264.7 cell model of lipopolysaccharide (LPS)-induced in ammation and murine models of acetic acid-and carrageenan-induced in ammation [14].…”
Section: Introductionmentioning
confidence: 99%